Health Saving Technologies in the Activities of the Educator- Psychologist. (Journal of Educational Sciences, 2016)
This article discusses technologies will in the work of the psychologistteacher organizations in education, helping to successfully adapt the child not only in school but also outside it. Timely use of health-technology (Technology of Bazarnyi V.F., behavioral therapy, Rayhanskaya therapy, Neo-rayhanskaya therapy, Feldenkrais Method, Tai Chi, Zen therapy, rational emotive-behavioral therapy, kinesiology, dance movement therapy of Fleshtrening) will help preserve and improve the health of students, and it is also important for the whole society, because only healthy people are able to properly integrate into society. Only a healthy person physically, psychologically and most importantly be able to be active and to confront the difficulties and stressful situations.
Keywords: future technologies; psychologist; teacher; mental health; physical health; the ability to manage internal state; vitality